2003
DOI: 10.1073/pnas.1032899100
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of reward-related learning by cholinergic cell ablation in the striatum

Abstract: The striatum in the basal ganglia-thalamocortical circuitry is a key neural substrate that is implicated in motor balance and procedural learning. The projection neurons in the striatum are dynamically modulated by nigrostriatal dopaminergic input and intrastriatal cholinergic input. The role of intrastriatal acetylcholine (ACh) in learning behaviors, however, remains to be fully clarified. In this investigation, we examine the involvement of intrastriatal ACh in different categories of learning by selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 32 publications
(53 reference statements)
8
59
0
1
Order By: Relevance
“…Microdialysis studies have shown that when rats used response strategies rather than spatial strategies for learning, striatal ACh release increased (Chang et al, 2003). Moreover, selective ablation of striatal cholinergic neurons impairs procedural learning in mice (Kitabatake et al, 2003). Thus, the enhancement in striatal cholinergic neurotransmission, after oral UMP administration, that we observe (e.g.…”
Section: Discussionsupporting
confidence: 53%
“…Microdialysis studies have shown that when rats used response strategies rather than spatial strategies for learning, striatal ACh release increased (Chang et al, 2003). Moreover, selective ablation of striatal cholinergic neurons impairs procedural learning in mice (Kitabatake et al, 2003). Thus, the enhancement in striatal cholinergic neurotransmission, after oral UMP administration, that we observe (e.g.…”
Section: Discussionsupporting
confidence: 53%
“…ChAT interneuron ablation in the striatum has been previously performed using proteinaceous toxins coupled to specific antibodies (29)(30)(31)(32). Unfortunately, whereas ChAT interneuron ablation was apparent after ChAT-saporin (SAP), we also found reductions in ChAT immunoreactivity, qualitative changes in ChAT cell morphology, and patchy cell loss after treatment with IgG-SAP, even at low doses (Fig.…”
Section: Methodsmentioning
confidence: 71%
“…We found an immunotoxin that has been used previously to target striatal ChAT interneurons (29)(30)(31)(32) to produce nonspecific effects (Fig. S1).…”
Section: Significancementioning
confidence: 99%
“…For instance, acetylcholinedepleting striatal lesions have been shown to disrupt appetitive, but spare aversive, learning (Kitabatake et al, 2003). Furthermore, both scopolamine (Sharf et al, 2006;Pratt and Kelley, 2004;Tikhonravov et al, 1997) and mecamylamine (Levin et al, 2000) tend to suppress foodreinforced lever pressing.…”
Section: Discussionmentioning
confidence: 99%